Resiliency: A dynamic view of liquidity - Alexander Kempf; Daniel Mayston; Monika Gehde-Trapp; Pradeep K. Yadav (University of Cologne, Centre for Financial Research (CFR), 2015)
This paper investigates resiliency to provide a dynamic perspective on liquidity. We define resiliency as the rate of mean reversion in liquidity. Resiliency increases with the proportion of patient traders, decreases with order arrival rate, and increases with tick size; providing strong support for the Foucault, Kadan, and Kandel (2005) model. Resiliency is also greater when information-related risks are lower. Algorithmic trading is associated with higher resiliency, but less so for smaller stocks and in information-intensive periods. Our results for spread and depth resiliency are similar, and robust with respect to the order book depth at which liquidity is measured.
Keywords: G10; G14; 330; Liquidity; Resiliency